A Short Review of Some of the Factors Affecting the Breakdown Strength of Insulating Oil for Power Transformers - Danikas, M.; Sarathi, R.; Morsalin, S. (Engineering, Technology & Applied Science Research, 2020)
The present short review investigates some of the factors affecting the breakdown strength of transformer oil. Factors such as the conditioning effect, effect of oil flow, influence of impurities, type of applied voltage and electrode configuration and geometry are further discussed. It should be noted that this review does not discuss the effect of factors such as area, volume and capacitance. Velocity, impurities, electrodes’ shape and the type of applied voltage are among the factors documented to have a significant effect on breakdown strength.